A Privileged Point of View: Effects of Subjective Socioeconomic Status on Naïve Realism and Political Division. (February 2021) - Brown-Iannuzzi, Jazmin L.; Lundberg, Kristjen B.; Kay, Aaron C.; Payne, B. Keith
In the United States, both economic inequality and political conflict are on the rise. We investigated whether subjective socioeconomic status (SSS) may help explain why these dual patterns emerge. We hypothesized that higher SSS may increase naïve realism—the belief that one perceives the world as it is, rather than as interpreted through one's own knowledge and beliefs—regarding political issues. Using a representative sample of the American electorate, we found that higher SSS predicted more political naïve realism toward those from a different political party (Study 1). The remaining experiments examined the causal relationship between SSS and political naïve realism (Studies 2–5). We extended these findings by investigating whether SSS influenced participants' willingness to exclude those with contrary views from a vote (Studies 4 and 5). Together, these studies demonstrate that SSS enhances political naïve realism and can lead to the exclusion of others with contrary opinions.